2015
DOI: 10.1063/1.4928572
|View full text |Cite
|
Sign up to set email alerts
|

Heat generation above break-even from laser-induced fusion in ultra-dense deuterium

Abstract: Previous results from laser-induced processes in ultra-dense deuterium D(0) give conclusive evidence for ejection of neutral massive particles with energy >10 MeV u−1. Such particles can only be formed from nuclear processes like nuclear fusion at the low laser intensity used. Heat generation is of interest for future fusion energy applications and has now been measured by a small copper (Cu) cylinder surrounding the laser target. The temperature rise of the Cu cylinder is measured with an NTC resistor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 26 publications
1
27
0
Order By: Relevance
“…Laser-induced nuclear fusion in D(0) gives heat above break-even, as reported in Ref. [15]. Recent studies show that the MeV particles ejected from H(0) decay within 100 ns [1618].…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Laser-induced nuclear fusion in D(0) gives heat above break-even, as reported in Ref. [15]. Recent studies show that the MeV particles ejected from H(0) decay within 100 ns [1618].…”
Section: Introductionmentioning
confidence: 86%
“…However, when the distance to the second (outer) collector is increased, this picture changes to give a too short TOF and a too high signal at the outer collector as in Refs. [15,17,23]. The particles then move with a velocity close to the speed of light c and the TOF distribution is sharper at long distance [17].…”
Section: Introductionmentioning
confidence: 99%
“…15 The total energy in the ejected particles is so large that the nuclear reaction process is above breakeven. 16 The nuclear processes taking place are both laserinduced nucleon + nucleon annihilation-like processes [2][3][4][5][6] and ordinary D + D fusion partly of the muon-catalyzed type. That ordinary D + D fusion takes place is shown by neutron detection 17 and by TOF mass spectrometry studies.…”
Section: Introductionmentioning
confidence: 99%
“…(The so called scienti c break-even in NIF [24] is a special de nition of break-even which is not of practical interest). The process observed in D(0) [9] was mixed as can be concluded now, using both muon-induced fusion and annihilation energy generation. At the time of the experiment, the annihilation process had not yet been identi ed, so the process was thought to be laserinduced ICF using the D + D reaction.…”
Section: B Annihilationmentioning
confidence: 62%
“…The particle velocity measured by direct timing and by decay dilation corresponds to 10-500 MeV u − 1 [10,14,15]. By using two [9] and three [12] collectors in line, it is found that the fast particles have mass and that they penetrate through mm thick metal with some attenuation and a slight delay. Magnetic de ection studies con rm that many of the initially formed particles are neutral [16] and that the mass of the charged particles is less than 1 u, thus mesons and muons.…”
Section: Introductionmentioning
confidence: 99%